2015
DOI: 10.11144/javeriana.upsy14-1.shah
|View full text |Cite
|
Sign up to set email alerts
|

Felicidad y esperanza subjetiva

Abstract: a b S t r a c tThe aim of this research is to examine the relationships between subjective happiness and hope. The participants were 435 university students. In this study, the Integrative Hope Scale and the Subjective Happiness Scale were used. The relationships between were examined using correlation analysis and Structural Equation Model (SEM). In correlation analysis, trust and confidence, positive future orientation, and social relations and personal value sub factors of hope were found positively related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Moreover, interventions directed towards developing hope have been effective in decreasing the development of psychological disorders (Rustøen et al 2011) and PTSD (Yousefi et al 2016). On the other hand, hope has a positive correlation with subjective happiness (Sariçam 2015) and subjective well-being (Kato and Snyder 2005;Satici 2016;Shenaar-Golan 2017;Yalçın and Malkoç 2015). Thus, the finding here that hope appears to develop mental health by decreasing fear can be said to exhibit similar features with the findings of previous research.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, interventions directed towards developing hope have been effective in decreasing the development of psychological disorders (Rustøen et al 2011) and PTSD (Yousefi et al 2016). On the other hand, hope has a positive correlation with subjective happiness (Sariçam 2015) and subjective well-being (Kato and Snyder 2005;Satici 2016;Shenaar-Golan 2017;Yalçın and Malkoç 2015). Thus, the finding here that hope appears to develop mental health by decreasing fear can be said to exhibit similar features with the findings of previous research.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, interventions programs that facilitate hope decrease psychological symptoms (Rustøen et al 2011). On the other hand, hope has a positive association with subjective happiness (Sariçam 2015) and subjective well-being (Kato and Snyder 2005;Satici 2016; Shenaar-Golan 2017; Yalçın and Malkoç 2015). When these findings are taken as a whole, hope can be thought of as playing a protective role that stimulates good mental health and counteracts psychological problems caused by COVID-19.…”
Section: Hope As a Factor In Preventing Poor Mental Healthmentioning
confidence: 99%
“…Happiness is the biggest goal that every human being wants to achieve (Vitrano, 2010). The individual obtains happiness through fulfilling his needs, accepting all his or her shortcomings and adapting to his environment and social expectations (Sariçam, 2015). The activities of each are a manifestation of his desire to gain happiness.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, hope can be considered a protective factor for mental well-being (Satici et al, 2023), and evidence suggests that hope underpins the recovery process in mental illness and defines it as the beginning of recovery, along with personal and environmental factors that converge in healing (Acharya & Agius, 2017). Research has demonstrated that hope is positively associated with personal growth (Vuyk & Codas, 2022), occupational engagement and career development (Vuyk et al, 2020), subjective happiness (Sariҫam, 2015), well-being (Shenaar-Golan, 2017) and resilience (Senger, 2023). Resilience is the personal capacity to adapt to trauma, adversity, stressors and tragedies (Wells et al, 2012), and is considered a protective factor for psychological disorders (Satici et al, 2023).…”
Section: Introductionmentioning
confidence: 99%